Nuclear-Overhauser-enhanced MR imaging of 31P-containing metabolites: multipoint-Dixon vs. frequency-selective excitation - Rink, Kristian; Berger, Moritz C.; Korzowski, Andreas; Breithaupt, Mathies; Biller, Armin; Bachert, Peter; Nagel, Armin Michael (Magnetic resonance imaging, 2015)
The purpose of this study is to develop nuclear-Overhauser-enhanced (NOE) [1H]-31P magnetic resonance imaging (MRI) based on 3D fully-balanced steady-state free precession (fbSSFP). Therefore, two implementations of a 3D fbSSFP sequence are compared using frequency-selective excitation (FreqSel) and multipoint-Dixon (MP-Dixon). 31P-containing model solutions and four healthy volunteers were examined at field strengths of B0=3T and 7T. Maps of the distribution of phosphocreatine (PCr), inorganic phosphate (Pi), and adenosine 5´-triphosphate (ATP) in the human calf were obtained with an isotropic resolution of 1.5cm (1.0cm) in an acquisition time of 5min (10min). NOE-pulses had the highest impact on the PCr acquisitions enhancing the signal up to (82 ± 13) % at 3T and up to (37 ± 9) % at 7T. An estimation of the level of PCr in muscle tissue from [1H]-31P MRI data yielded a mean value of (33 ± 8) mM. In conclusion, direct [1H]-31P imaging using FreqSel as well as MP-Dixon is possible in clinically feasible acquisition times. FreqSel should be preferred for measurements where only a single metabolite resonance is considered. MP-Dixon performs better in terms of SNR if a larger spectral width is of interest.